Keterkaitan Alih Fungsi Lahan dengan Perubahan Aktivitas di Tembalang (Kelurahan Tembalang,Bulusan, dan Mangunharjo) Semarang - Alif Firdaus Rison Waskito; Bitta Pigawati (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Semarang is the capital of Central Java province with a population in 2016 has reached 1,694,412 inhabitants. Especially in District Tembalang the population in 2016 has reached 172 525 inhabitants a lot of changes and developments that have occurre. With a dense population causes a lot of activity going, so that the rapid population growth and the increasing number of activities that exist in the Village Tembalang, Bulusan and Mangunharjo, resulting in a lot of land conversion happens. The purpose of this study is to assess the linkage of land conversion to changes in activity in Tembalang (Tembalang, Bulusan, and Mangunharjo village) Semarang. The method used in this research is using descriptive quantitative method. Results of this study are Tembalang village has a population of 5,519 inhabitants in 2015. Topography and soil type 2.5% - 40% with dark brown soil types mediterranean. Bulusan village has a population of 5,125 inhabitants in 2015. Topography and soil type 0% - 40% with dark brown soil types mediterranean. Mangunharjo village has a population of 8,468 inhabitants in 2015. Topography and soil type 0% - 40% with dark brown soil types mediterranean. Land conversion in the Tembalang, Bulusan, and Mangunharjo village with a total percentage of 39.7% is comprised of 16.1% in the Mangunharjo village, 12.8% in the Bulusan village, and 10.1% in Tembalang village. Changes in activity in Tembalang, Bulusan, and Mangunharjo village, are educational activities for 4697 activities, the activities of some 126 trade and service activities, and human settlement activity as much as 351 activities. Occurred linkages between land use change with changes in the activity of trade in services and settlement activity in Tembalang, Bulusan and Mangunharjo village. The significant value of trade and services activity is 0.027 < 0.05 which means there is influence and linkage, then the settlement activity is 0.018 < 0.05 which also means has influence and linkage.